The effectiveness of inquiry lesson-based digestive system materials for training students' science literacy ability - Rina Oktaviana; Eni Nuraeni; Amprasto Amprasto (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Learning biology needs to seek the formation of students who have scientific literacy skills. This ability is closely related to understanding science in everyday life. This study aims to analyze the increase in scientific literacy skills by implementing inquiry lesson-based worksheets on the material of the human digestive system. The research method used was quasi-experimental with a non-randomized control group pre-test and post-test research design. Participants are two classes XI MIPA. The sampling technique is cluster random sampling. That is, two classes XI MIPA were randomly selected. Classes XI MIPA 5 and XI MIPA 6, each consisting of 32 students, where one was the control class and the other was the experimental class. Data were obtained using 10 PISA frameworks scientific literacy questions in the form of valid and reliable multiple choice questions. The results showed a significant difference, as evidenced by the results of hypothesis testing with Sig. (2-tailed) = 0.000 < 0.05, then H0 rejected and Ha accepted. There is a difference in t-count experimental class and t-count where is the control class t-count the experimental class is greater than t-count the control class is 53.82 > 21.997 so that the scientific literacy abilities of students from the two classes have significant differences.Abstrak Pembelajaran biologi perlu mengupayakan terbentuknya peserta didik yang memiliki kemampuan literasi sains. Kemampuan ini erat hubungannya dengan pemahaman sains di dalam kehidupan sehari-hari. Penelitian ini bertujuan untuk menganalisis peningkatan kemampuan literasi sains melalui implementasi LKPD berbasis Inquiry Lesson pada materi sistem pencernaan manusia. Metode penelitian yang digunakan yaitu quasi eksperimental dengan desain penelitian Pre-test and Post-test Non-randomized Control Group. Partisipan merupakan dua kelas XI MIPA. Teknik penarikan sampel menggunakan cluster random sampling, yaitu dipilih secara acak dua kelas XI MIPA. Kelas XI MIPA 5 dan XI MIPA 6 yang masing-masing terdiri dari 32 peserta didik, dimana salah satu sebagai kelas kontrol dan yang lain sebagai kelas eksperimen. Data diperoleh dengan menggunakan soal literasi sains berframework PISA berjumlah 10 dengan bentuk soal pilihan ganda yang telah valid dan reliabel. Hasil penelitian menunjukkan perbedaan yang signifikan dibuktikan melalui hasil uji hipotesis dengan Sig. (2 tailed) = 0,000 < 0,05, maka H0 ditolak dan Ha diterima. Terdapat perbedaan pada t-hitung kelas eksperimen dan t-hitung kelas kontrol dimana t-hitung kelas eksperimen lebih besar dari t-hitung kelas kontrol yaitu 53,82 > 21,997, sehingga kemampuan literasi sains peserta didik dari kedua kelas tersebut memiliki perbedaan yang signifikan.